Truth-telling in queer performativity: A critique of the modern truth dispositif - Vilches Rosales, Noam (Revista Ethika+, 2020)
The gender power device will be problematized using the analysis of queer performance from Butler’s perspective. For this, on one hand truthful telling will be addressed in Plato’s dialogues and on the other hand the modern concept of truth and its normative implications from a Foucauldian point of view. Finally, it will be explained how the disruption of gender dissident communities meet parrhesiastic criteria, how this has allowed it to confront modern criteria and the contribution that this could make to the philosophical task